2020
DOI: 10.34133/2020/5618021
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Mechanical Properties of Graphene/Cu Nanocomposites with In-Plane Negative Poisson’s Ratios

Abstract: Negative Poisson’s ratio (NPR), also known as “auxetic”, is a highly desired property in a wide range of future industry applications. By employing molecular dynamics (MD) simulation, metal matrix nanocomposites reinforced by graphene sheets are studied in this paper. In the simulation, single crystal copper with crystal orientation 11 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…, where E is the total energy between a pair of Cu atom and C atom; r is the distance between Cu atom and C atom; r c is the cutoff distance; ε is the well depth and δ is an equilibrium distance. In the present work, ε = 0.019996 eV, δ = 3.225 Å [20,51,52] and r c = 5 δ. The interactions between the incident S atom with C, Cu, and other S atoms were calculated with the ZBL repulsive potential [53].…”
Section: Simulation Methodologymentioning
confidence: 74%
See 1 more Smart Citation
“…, where E is the total energy between a pair of Cu atom and C atom; r is the distance between Cu atom and C atom; r c is the cutoff distance; ε is the well depth and δ is an equilibrium distance. In the present work, ε = 0.019996 eV, δ = 3.225 Å [20,51,52] and r c = 5 δ. The interactions between the incident S atom with C, Cu, and other S atoms were calculated with the ZBL repulsive potential [53].…”
Section: Simulation Methodologymentioning
confidence: 74%
“…Graphene is a two-dimensional (2D) sheet consisting of covalently bonded sp 2hybridised carbon atoms with exceptional electrical, mechanical and thermal properties [15][16][17][18]. Graphene is considered an attractive reinforcement to enhance the mechanical properties (such as hardness and strength) of MMCs, including Gr-Cu [19][20][21][22][23][24][25], Gr-Cu-W [26], Gr-Fe [27], and Gr-Al [28][29][30]. Recent studies have shown that graphene can improve the arc erosion resistance of MMCs.…”
Section: Introductionmentioning
confidence: 99%
“…The long-range interactions were captured by the particle-particle particle-mesh (PPPM) method. In addition, the Lorentz-Berthelot mixing rule was employed to describe the Lennard-Jones (L-J) atomic interactions inside HEA matrix and GO sheet [ 50 , 51 ]. The dislocation extraction algorithm (DXA) technique [ 52 ] was employed to diagnose dislocation movements in nanopillars.…”
Section: Methodsmentioning
confidence: 99%
“…Except for the good mechanical and bacterial properties, the corrosion resistance and biocompatibility also determine the survival of the implants. It is well known that grain refinement is widely used to improve the mechanical properties, corrosion resistance, , and biocompatibility of titanium alloys and other materials. In the physiological environment, numerous grain boundaries and dislocations brought by grain refinement provided numerous nucleation sites for the quick formation and growth of the uniform and compact passive film to provide better corrosion protection to the alloys. Furthermore, grain refinement also modifies the hydrophilicity to promote the adhesion and proliferation of the human bone marrow mesenchymal stem cells and osteoblasts on the surface of titanium alloys. , Therefore, it is reasonable to speculate that the grain refinement will further improve the comprehensive performances of Cu-containing titanium alloys, and the successful preparation of the Ti6Al4V-5Cu UG alloy provides an excellent material basis for our research.…”
Section: Introductionmentioning
confidence: 99%